GAYA BAHASA NIDĀ’ DALAM SURAT YUSUF (PENDEKATAN STILISTIKA) - Abdu Rabbi Faqihuddin (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2020)
The purpose of this study is to describe the form of nidā', kinds of munādā, and the meanings contained in the style of nidā’ language and kalām afterward. This research discusses the style of nidā’ with the object of Sura Yusuf, using stylistic analysis. The method used in this research is a qualitative descriptive method, which is library research.The problem raised in this research is how the form and kinds of nidā’ and munādā, the meaning of the style of nida’ and later kalam in the sura Yusuf. The results obtained in this research are, in the sura Yusuf there are two forms of nidā’, namely lafdziyyah and ghairulafdziyyah, and three kindsmunādā, namely mudhāf, nakirahmaqshūdah, and mufradalam. While the nidā’ in the sura Yusuf followed by four kalām namelyamr, nahy, khabar, and istifhām with the meaning of haqīqī and majazī.